Relación de la TSH y las alteraciones electrocardiográficas, en los pacientes hospitalizados en el servicio de Medicina Interna del Hospital Isidro Ayora de Loja desde abril - noviembre 2013. - Chacón Valdiviezo, Gabriela de los Ángeles (2013)
The gland thyroid and the heart are related closely physiologically; concept refroze by predictable change of the cardiovascular function of the different thyroid disorders. The knowledge and the identification of this relationship allows a diagnosis and early and effective treatment, as euthyroid states lead to the normalization of the cardiovascular disorders in most patients who suffer it. In this study were reviewed 40 selected cases by damage in the rhythm in their electrocardiograms, this group was determined the TSH through blood sample, in order to determine if the cardiac arrhythmias have or no relationship with the value of the TSH, know what is the thyroid hormone altering and the most common cardiac arrhythmia in this population. The participants were hospitalized in the Internal Medicine department of the hospital Isidro Ayora of Loja. It was necessary electrocardiogram collection as thyroid profile. Electrocardiograms were taken with Internal Medicine and External Consultation equipment, the TSH was determinate with equipment from two laboratories: Hospital laboratory Isidro Ayora of Loja and the laboratory of the Credit Union Vicentina “Manuel Esteban Godoy Ortega”, whose technique used is electrochemiluminescence and ELISA. The TSH reference range with which we worked was the values ​​were proposed by the American Association of Clinical Endocrinologists in May, 2013, TSH between 0.3 – 1.99 uUl/ml low normal; 2.0- 2.99 uUI/ml; Normal 3.0uIl/ml high normal. Was verified effectively that in the population with electrocardiogram alterations were mostly patients with alterations in the TSH value, the most frequent electrocardiographic alterations were: Atrial Fibrillation, Atrial Flutter, Complete Right Bundle Branch Block, extrasystoles Supraventricular and Ventricular extrasystoles. However, Atrial Fibrillation arrhythmia was most involved in the study group, documenting in most of the low TSH group, the half of high TSH and less of the half of euthyroid.